The narrative of an ordinary member of language community: WHERE and WHY is dialecticity of a locality created - Aliūkaitė, Daiva; Mikulėnienė, Danguolė (Lietuvių kalba, 2019)
The paper aims to explore where and why an ordinary member of language community creates the dialecticity of a locality and evaluate whether (and how) the dialect artefact of an ordinary member of language community is related with the dialecticity recognised and estimated by researchers, or, in other words, discuss the interaction of the emic and etic perspectives. The empirical basis for the discussion about the interaction of the emic and etic perspectives is formed on the verbalised and visualised language attitudes of the ordinary members of language community and the data of the text-stimuli perceptions gathered during the project “The Position of Standard Language in the Mental Map of the Lithuanian Language” carried out in 2014–2016 and supplied with the data of the ongoing project “Distribution of Regional Variants and Quasistandard Language at the Beginning of the 21st Century: Perceptual Approach (Perceptual Categorisation of Variants”, 2017–2019. The respondents of both projects are the first-fourth year grammar school pupils whom the scholars associate with the emic perspective. The first attempt concerned the data related with the verbalised and visualised (in the drawn maps) language attitudes of 1.415 teenagers; the second one analysed the data related with the verbalised and visualised (in the drawn maps) language attitudes of 1.064 youngsters and the data of the perception of the text-stimuli recorded in an adequate dialect. Both projects are interrelated with regard to the subject matter and the pursued goals: in the first case, an attempt was made to analyse the geolinguistic competence of an ordinary member of language community; in the second one, an additional aspect of the perceptual abilities of an ordinary member of language community was considered. During the performance of the two projects the essential criterion for the selection of the locations in the regions of Lithuania to be explored was whether they were (non)marked by dialect. Hence the respondent groups were formed in the regiolect and/or geolect zones, and in the second project the task of the text-stimuli perception had motivated the inclusion of the Lithuanian cities. The problem of how an ordinary member of language community creates the dialecticity of a location has been approached on the basis of the data given in the drawn maps presented in the two projects. The participants of the first project have drawn the so called perceptual isoglosses in two maps, i.e. in one map they have marked the areas where people speak in dialect and, in the other, where standard language was used. Meanwhile, the participants of the second project in their drawn maps related the linguistic homeland with other locations due to the similarity (or simultaneity) of expression. They also had to draw the maps of standard language and, in addition, localise 8 text-stimuli given to them for assessment which contained the 14–19 seconds fragments of spontaneous speech representing various regiolectic zones. To summarise the obtained results, it should be claimed that etic and emic discourses should be essentially related to the cause and effect factor. The narrative of an ordinary member of language community not only reveals the specific interior relationships but is also affected from outside. Such an insight is determined by the interaction between the created dialecticity of a locality and the dialecticity of localities legitimated in scientific discourse. The results obtained in both projects on perceptual dialectology show that the dialecticity of a locality has been constructed on the basis of adequate etic information: it is obvious from the drawn maps that dialecticity is attracted by the localities that are highly dialect-oriented, i.e. the geolectic and regiolectic areas. This assumption is based on the localisation of the text-stimulus having the most distinct features of dialect which confirms that dialect recognition by the ordinary members of language community does not enter into conflict with the researcher’s evaluation from outside. Thus it shows that localities do consistently attract the text-stimuli having the most distinct features of dialect. Meanwhile, as a place of dialect levelling, the capital (or any city) accurately correlates with the NORM reflection of traditional dialectology. The paper summarises that it is not clear yet in what ways the constructors of the narrative from inside are affected by the narratives from outside. There is no tradition formed in the works on perceptual dialectology and no adequate methodological instruments have been devised which might help to find out the sources of knowledge, images and attitudes of the ordinary members of language community. Hence, in order to more clearly describe the relationship between the narrative of a researcher and that of an ordinary member of language community it would be reasonable to move an additional step forward – to expand the instrumentarium and methods of research by including the reflections of the ordinary members of language community regarding the knowledge, images and attitudes that they possess in the field of dialecticity. Thus a new perspective in dialectology should be initiated.